Activating a high-spin iron(II) complex to thermal spin-crossover with an inert non-isomorphous molecular dopant - Halcrow, Malcolm A; Vasili, Hari Babu; Pask, Christopher M; Kulak, Alexander N; Cespedes, Oscar (Dalton transactions : an international journal of inorganic chemistry, 2024)
[Fe(bpp) ][ClO ] (bpp = 2,6-bispyrazol-1-ylpyridine; monoclinic, 2/ ) is high-spin between 5-300 K, and crystallises with a highly distorted molecular geometry that lies along the octahedral-trigonal prismatic distortion pathway. In contrast, [Ni(bpp) ][ClO ] (monoclinic, 2 ) adopts a more regular, near-octahedral coordination geometry. Gas phase DFT minimisations (ω-B97X-D/6-311G**) of [M(bpp) ] complexes show the energy penalty associated with that coordination geometry distortion runs as M = Fe (HS) ≈ Mn (HS) < Zn ≈ Co (HS) ≲ Cu ≪ Ni ≪ Ru (LS; HS = high-spin, LS = low-spin). Slowly crystallised solid solutions [Fe Ni (bpp) ][ClO ] with = 0.53 (1a) and 0.74 (2a) adopt the 2 lattice, while = 0.87 (3a) and 0.94 (4a) are mixed-phase materials with the high-spin 2/ phase as the major component. These materials exhibit thermal spin-transitions at = 250 ± 1 K which occurs gradually in 1a, and abruptly and with narrow thermal hysteresis in 2a-4a. The transition proceeds to 100% completeness in 1a and 2a; that is, the 26% Ni doping in 2a is enough to convert high-spin [Fe(bpp) ][ClO ] into a cooperative, fully SCO-active material. These results were confirmed crystallographically for 1a and 2a, which revealed similarities and differences between these materials and the previously published [Fe Ni (bpp) ][BF ] series. Rapidly precipitated powders with the same compositions (1b-4b) mostly resemble 1a-4a, except that 2b is a mixed-phase material; 2b-4b also contain a fraction of amorphous solid in addition to the two crystal phases. The largest iron fraction that can be accommodated by the 2 phase in this system is 0.7 ± 0.1.